(untitled) (Research, Society and Development, 2021)
Seed analysis is usually performed by destructive samples with time-consuming methods. Treatments that improve seed vigor are suggested based on bioassays and protocols for most plants. This includes the use of images to assess quality and pro- vide information that supports decisions. However, instrumental cost has not made these technologies widely used. The objective of this research was to study biophotonic images generated by low cost technologies - cold plasma scanner or gas discharge visualization (GDV) and speckle laser (BSL) - to evaluate the germination of adzuki beans seeds treated with ultrahigh dilutions (UHD). The research was carried out at the EPAGRI Homeopathy and Plant Health Laboratory, with a post-graduate support at the State University of Santa Catarina (UDESC). The images of the seeds were diagnosed mathematically, before and after germination, using “Local Connected Fractal Dimension Analysis” (LCFD) and “Time History Speckle Pattern” (THSP). The results show that the images identify the effects of high dilution - Bryonia alba and Silicea terra, at 6, 12 and 30 CH (centesimal hahnemannian dilution order) - on the seeds of azuki beans. There were statistically differences (p < 1% and p < 5%) of the treatments in relation to the control: water. Only Silicea terra 30CH inhibited seed germination. The signals found in the BSL images of the seeds were superior to the GDV signals, showing an average of 89% correct responses (BSL) against 87% (GDV).